Criminal Confrontation of Hate Crimes via the Metaverse A Study in Light of the Yazidi Genocide - Al-Ghalib, Rami (Journal of Legal Sciences, 2026)
This research examines the criminal confrontation of hate crimes committed through the Metaverse, a vast electronic sphere that enables incitement to hatred and the ideological justifications of terrorism aimed at excluding religiously and ethnically different groups from social participation. The significance of the study lies in addressing a novel issue and highlighting a new pattern of organized crime in the post-globalization era, by linking technological developments to criminal liability and exploring mechanisms of national and international response. The research problem centers on whether existing criminal laws are capable of addressing hate crimes within the Metaverse, and what lessons may be drawn from the Yazidi genocide perpetrated by the terrorist organization ISIS, which relied on ideological indoctrination through cultural and media tools, exploiting cyberspace to promote the exclusion of “the other” from the social sphere. To address this problem, the study adopts a descriptive-analytical and comparative methodology, analyzing provisions of national criminal law and relevant international conventions, while comparing them with the realities of the Yazidi genocide, which demonstrates how hate speech can escalate into genocide. The study concludes that current legislative frameworks are insufficient to combat hate crimes in emerging virtual spaces. It therefore calls for a specific legal framework for the Metaverse, strengthened mechanisms of international cooperation, and precise digital evidentiary rules. Moreover, the Yazidi genocide provides a critical reference for understanding the dangers of digital hatred and the necessity of addressing it within the Metaverse itself before it evolves into virtual genocide.